Education in the Perspective of the ‘Inner Image’ - Marek Jeziorański (Paedagogia Christiana, 2024)
The article fits into the field of anthropology and pedagogical teleology. It identifies three basic anthropological models. The basis for the distinction of the anthropological models described is the category of the ‘inner image’ of the pupil, understood as the deepest truth about the human being; a reality revealed through reflection and at the same time containing elements of mystery, which is why it cannot be unambiguously identified and fully defined but requires an effort to be discovered and then pursued. The three models proposed are as follows: 1. A pedagogy based on the ‘inner image;’ 2. A pedagogy that excludes the ‘inner image;’ 3. A pedagogy of the tacit ‘inner image.’ The theoretical proposals presented are justified by the ideological trends present in pedagogy and their exemplary consequences for educational practice are shown.